Junian Latinity in the Roman Empire Volume 1 - López Barja, Pedro; Doria, Carla Masi; Roth, Ulrike (Edinburgh University Press, 2023)
This book offers new historical, legal and literary explorations of a status held by uncountable formerly enslaved persons in the Roman Empire: Junian Latinity. It is the first book in any language to provide comprehensive multi-disciplinary study of this status. Divided in two parts, the book sets the scene with six chapters that discuss the legal innovations that created Junian Latinity, as well as the historical contexts in which the status was conceived and in which it developed – from the late republican period to the early medieval world. Four chapters in the second book part offer then new research on key Latin literary texts to provide fresh insights into the role of Junian Latinity in Roman imperial society. The book makes a strong case for the centrality of Junian Latinity in the Roman Empire and the importance of its modern study.